Enablers and barriers to implementing obesity assessments in clinical practice: a rapid mixed-methods systematic review. Issue 11 (29th November 2022) - Atlantis, Evan; Chimoriya, Ritesh; Seifu, Canaan Negash; Peters, Kath; Murphy, Gill; Carr, Bernadette; Lim, David; Fahey, P
Abstract : Objectives: This systematic review aims to improve our knowledge of enablers and barriers to implementing obesity-related anthropometric assessments in clinical practice. Design: A mixed-methods systematic review. Data sources: Medline, Embase and CINAHL to November 2021. Eligibility criteria: Quantitative studies that reported patient factors associated with obesity assessments in clinical practice (general practice or primary care); and qualitative studies that reported views of healthcare professionals about enablers and barriers to their implementation. Data extraction and synthesis: We used random-effects meta-analysis to pool ratios for categorical predictors reported in ≥3 studies expressed as pooled risk ratio (RR) with 95% CI, applied inverse variance weights, and investigated statistical heterogeneity (I 2 ), publication bias (Egger's test), and sensitivity analyses. We used reflexive thematic analysis for qualitative data and applied a convergent integrated approach to synthesis. Results: We reviewed 22 quantitative (observational) and 3 qualitative studies published between 2004 and 2020. All had ≥50% of the quality items for risk of bias assessments. Obesity assessment in clinical practice was positively associated with patient factors: female sex (RR 1.28, 95% CI 1.10 to 1.50, I 2 99.8%, mostly UK/USA), socioeconomic deprivation (RR 1.21, 95% CI 1.18 to 1.24, I 2 73.9%, UK studies), non-white race/ethnicity (RR 1.27, 95% CI 1.03 to 1.57, I 2 99.6%) and comorbidities (RR 2.11, 95% CI 1.60 to 2.79, I 2 99.6%, consistent across most countries). Obesity assessment was also most common in the heaviest body mass index group (RR 1.55, 95% CI 0.99 to 2.45, I 2 99.6%). Views of healthcare professionals were positive about obesity assessments when linked to patient health (convergent with meta-analysis for comorbidities) and if part of routine practice, but negative about their role, training, time, resources and incentives in the healthcare system. Conclusions: Our evidence synthesis revealed several important enablers and barriers to obesity assessments that should inform healthcare professionals and relevant stakeholders to encourage adherence to clinical practice guideline recommendations.